Comparison of negative pressure wound therapy with conventional wound care in the treatment of sternal wound infection after cardiac surgery: A meta-analysis with trial sequential analysis - Si He; Na Tang; Sha Li (PLoS ONE, 2025)
Background Negative pressure wound therapy (NPWT) has become a popular treatment option for sternal wound infection (SWI). However, it remains uncertain whether the therapeutic benefits of NPWT are superior to conventional wound care. This study aimed to systematically evaluate the therapeutic effects of NPWT on SWI compared to conventional wound care through meta-analysis. Methods A comprehensive search of PubMed, Web of Science, Embase, and the Cochrane Library databases was conducted from inception to April 29, 2024 for all potential studies. The pooling of dichotomous outcome data was achieved using relative risk (RR), with results presented within a 95% confidence interval (CI). We utilized the standard mean difference (SMD) and 95% CI for continuous outcomes. Heterogeneity test, publication bias assessment, sensitivity analysis, and trial sequential analysis (TSA) were conducted. Publication bias was detected through the Begg’s and Egger’s tests. Software R 4.3.1, Stata 12.0, and TSA v0.9.5.10 Beta software were utilized for all analyses. Results Out of 1832 articles identified, 10 were included in this study. The overall results revealed that NPWT significantly decreased the sternal wound reinfection (SWRI) rate (RR [95% CI] = 0.179 [0.099 to 0.323], 95% prediction interval [PI]: 0.082 to 0.442), in-hospital mortality (RR [95% CI] = 0.242 [0.149 to 0.394], 95% PI: 0.144 to 0.461), and shortened the length of intensive care unit (ICU) stay (SMD [95% CI] = −0.601 [−0.820 to −0.382], 95% PI: −1.317 to 0.128) compared with conventional wound care. There was no significant difference in length of hospital stay (SMD [95% CI] = −0.402 [−0.815 to 0.012], 95% PI: −1.801 to 0.998) and treatment duration (SMD [95% CI] = −0.398 [−1.646 to 0.849], 95% PI: −16.340 to 15.543) between the NPWT group and control group. Further subgroup analysis demonstrated the benefits of NPWT in shortening hospitalization length in the European population (p < 0.05). Conclusion The present evidence corroborates that the application of NPWT in the treatment of SWI after cardiac surgery effectively reduces the SWRI incidence and in-hospital mortality while shortening the length of ICU stay.